Mobile Commerce - The Rising Dragon In The Digital Era (Trinity Journal of Management, IT & Media (TJMITM), 2016)
In today’s digital era mobile commerce is growing at a very  fast pace. It is contributing to the growth of e-commerce sales  in India. Mobile commerce is driving the revenue of retailers.  The way customers’ shop is changing due to the way technology  isused in the shopping process. The purpose of this paper is to  investigate the factors that influence customers’ to adopt mobile  shopping.Data is collected from West Delhi. Factor analysis is  used to extract factors that influence customers’ to adopt mobile  shopping. The results demonstrate that the most important  factors are Perceived Usefulness, Trust, Incentives, Convenience,  Consumption experience, Self -efficacys and Subjective norms.  The findings of the study helps to understand what encourages  the customers’ for mobile shopping .The result also helps retailers  in developing their strategies to encourage mobile shopping in  India.
Keywords: Mobile Shopping; Purchasing